Evaluation of the Practicality and Effectiveness of Microcontroller-Based Robotics Trainers as Learning Media - Wahyudi, Wahyudi; Jaya, Hendra; Sabara, Edy (Three E Science Institute, 2021)
The development of robotics technology occurred very rapidly in the industrial era of 4.0. Human interest in robot development is getting higher, and research related to robotics is increasingly emerging. One of these developments is the research of learning media, one of which is a robotics trainer. A robot is a mechanical device that can perform physical tasks, either using human supervision and control or using a program that has been logged in in the form of artificial intelligence. Based on this, a research study aimed to determine the stages of developing a microcontroller-based robotics trainer media as a learning medium at Universitas Negeri Makassar and producing a robotics trainer media that is valid, practical, and effective. The research method used is Research and Development (R&D) with the 4D development model theory, namely (1) defining, (2) designing, (3) development, (4) spreading. This study indicates that the microcontroller-based robotics trainer media developed on the media and material aspects are in the very right category to be used. The media trainer's implementation received student responses in the practical class in its use, and the results of student test scores after the performance had increased to be in the high category. The conclusion of these data states that the microcontroller-based robotics trainer media that has been developed is declared valid/suitable for use and practical and effective in its use.